2010
DOI: 10.1179/106698110x12640740712897
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of clinical judgments and criteria associated with mechanisms-based classifications of pain in patients with low back pain disorders: a preliminary reliability study

Abstract: Mechanisms-based classifications of pain have been advocated for their potential to aid understanding of clinical presentations of pain and improve clinical outcomes. However, the reliability of mechanisms-based classifications of pain and the clinical criteria upon which such classifications are based are not known. The purpose of this investigation was to assess the inter-and intra-examiner reliability of clinical judgments associated with: (i) mechanisms-based classifications of pain; and (ii) the identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
(35 reference statements)
1
24
2
Order By: Relevance
“…These systems are based on specific algorithms which possibly make it easier to agree on categories [12,22]. This study reflects current clinical practice where an overall clinical impression is made based on the signs and symptoms.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These systems are based on specific algorithms which possibly make it easier to agree on categories [12,22]. This study reflects current clinical practice where an overall clinical impression is made based on the signs and symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…The number of patients recruited in this reliability study is similar to the majority of published reliability studies on LBP classification systems [12,22]. However, the sample size calculation is based on specifying a zero value for kappa in the null hypothesis.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Pain mechanism classification systems (PMCSs) have been introduced into the diagnostic process for pain practitioners such as physical therapists (PTs) and physicians. [11][12][13] The clinical indicators of nociceptive, peripheral neuropathic, and central mechanisms have been used to classify patients' reports of pain.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary inter-and intraexaminer reliability study concluded that two therapists reliably diagnosed the dominant pain mechanism of patients with low back and leg pain, but concluded that a study with a larger sample of patients with multiple independent examiners was needed. 12 Evidence for discriminative validity of the classification system was established for categories of nociceptive, peripheral neuropathic, and central sensitization with a larger population of patients. 13 The PMCS described by Gifford and Butler 19 was modified and implemented into PT practice within the outpatient clinics of a rehabilitation hospital during the last 11 years.…”
mentioning
confidence: 99%